Geochemical distribution, fractionation and contamination assessment of heavy metals in marine sediments of the Asaluyeh port, Persian Gulf. (15th February 2017) - Delshab, Hossein; Farshchi, Parvin; Keshavarzi, Behnam
Abstract: In this study, total concentration and speciation of heavy metals in sediments of the Asaluyeh, one of the Iran's largest commercial ports, are investigated. 48 sediment samples were collected and analyzed for trace and major elements. Sediment quality guidelines along with calculated enrichment factors and trace metal profiles indicate that Asaluyeh port is threated by contamination, especially with respect to Hg and Cu. Normalization to Sc indicated high enrichment factors in the sediments following the decreasing order of: Hg > Cu > As > Ni > Zn > Pb ≈ Cr ≈ Mn > Co ≈ V ≈ Fe ≈ Al. Hg displayed the greatest potential ecological risk factor among sampling stations. The results of sequential extraction procedure revealed that in some stations > 50% of Mn, V, Cu and Zn occur in potentially mobile phases and therefore are more readily mobilized in the sediments of the study area. Highlights: This study assesses a comprehensive environmental risk of marine sediment trace metal pollution. This study evaluates geochemistry and health risk combined with the speciation of heavy metals. This study points the critical contaminated elements that need to be paid special attention.